Pyrazole-tethered heteroditopic ligands and their transition metal complexes: synthesis, structure, and reactivity - Mukherjee, Anuradha; Subramanyam, U.; Puranik, Vedavati G.; Mohandas, T. P.; Sarkar, A. (European Journal of Inorganic Chemistry, 2005)
Various pyrazole-based PN (2a-c) and N,N (3a-b) ligands have been synthesized. Using representative ligands, Ni-II, Co-II, Cu-II, and Cu-I complexes have been prepared and structurally characterized by crystallography. During complexation of Co-II and Cu-II salts, the phosphane part of the PN ligand oxidized to phosphane oxide. For N,N donor ligands, a dimeric chloro-bridged Ni-III complex was obtained. Ni-II complex 4 is an active catalyst for ethylene oligomerization. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheirn, Germany, 2005).
Keywords: cobalt; Copper; hemilabile ligands; Nickel; oligomerization; Pyrazole

Iron-nickel bimetallic nanoparticles for reductive degradation of azo dye orange G in aqueous solution - Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Applied Catalysis B-Environmental, 2008)
The degradation of Orange G, a monoazo dye, in aqueous solutions was investigated using Fe-Ni bimetallic nanoparticles. Transmission electron microscopy (TEM) of as-synthesized nanoparticles showed the presence of spherical particles having a size of 20-40 nm. X-ray photoelectron spectroscopy (XPS) did not detect the presence of nickel on the nanoparticle surface, which suggested a uniform distribution of both metals inside the particle core. Batch experiments with a minimum nanocatalyst loading of 3 g/L showed complete dye degradation after 10 min of reaction time. The degradation efficiency was linearly dependent on the initial dye concentration, pH of the solution and total Fe-Ni catalyst concentration. The efficiency increased with increasing Fe-Ni concentration and decreasing pH of the solution, but decreased with an increase in the dye concentration. The degradation rate followed first order reaction kinetics with respect to the dye concentration. High performance liquid chromatography-mass spectrometry (HPLC-MS) analysis of the degradation products revealed that the degradation mechanism proceeds through a reductive cleavage of the azo linkage resulting in the formation of aniline and surface-adsorbed naphthol amine derivatives. The latter are subsequently hydroxylated through an oxidative process. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Azo Dye; Degradation; iron; Nanoparticles; Nickel

On the change in bacterial size and magnetosome features for magnetospirillum magnetotacticum (MS-1) under high concentrations of zinc and nickel - Kundu, S.; Kale, A. A.; Banpurkar, Arun G.; Kulkarni, G. R.; Ogale, S. B. (Biomaterials, 2009)
The characteristic size, shape and specific alignment of magnetite crystals synthesized by magnetotactic bacteria is a highly coordinated process with precise control over magnetosome vesicle formation, uptake and transport of Fe, and magnetite biomineralization. Magnetosome membranes along with some specific membrane proteins regulate crystal nucleation and morphology of magnetite. Several previous works have indicated that the morphology of mature magnetite crystals is largely unaffected by environmental conditions, though some recent studies have shown the possibility of manipulation of the biomineralization process. In this study we have examined the effects of high concentrations of Zinc and Nickel on the growth of Magnetospirillum magnetotacticum (MS-1) and the corresponding magnetosome formation. Using various characterizations it is shown that the growth of the bacterial cells, as well as the size, shape and magnetosome chain alignment is significantly influenced in the presence of high concentrations of Zn or Ni. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biomineralization; magnetite; Magnetosome; Magnetospirillum magnetotacticum; Nickel; zinc

Methane reforming with carbon dioxide over La-Ni-x-Ce1-x mixed oxide catalysts - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Upendar, K.; Lingaiah, N.; Rao, Kamaraju Seetha Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2014)
La-Ni-x-Ce1-x mixed oxide (0 <= x <= 1) catalysts have been hydrothermally prepared, characterized by physico-chemical techniques and evaluated for CO2 reforming of methane. High conversions are achieved for both methane and carbon dioxide over the LaNi0.6Ce0.4O3 catalyst tested under the conditions of CO2/CH4/N-2 ratio of 80/80/80. (total flow rate = 240 mL/min), space velocity of 28,800 h(-1) and at a temperature of 800 degrees C. The H-2/CO ratio in the syngas is stable at 0.93 +/- 0.02. Exchanging Ni with Ce, rather than with La as reported in the literature, appears to be a better option for the improved performance of the catalysts.
Keywords: Carbon dioxide reforming; Catalysts; Cerium; Dry reforming; Hydrothermal synthesis; Lanthanum; Methane reforming; Mixed oxides; Nickel

Copper- and phosphine-free nickel(II)-catalyzed method for C-H bond alkynylation of benzothiazoles and related azoles - Patel, Ulhas N.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2018)
A phosphine-free nickel(II)-catalyzed method for the C(2)-H bond alkynylation of (benzo)thiazoles, (benz)imidazoles, and oxazoles is described. Well-defined and air-stable (Phen)NiCl2 catalyst efficiently catalyzes the coupling of diverse azoles with alkynyl bromides without the use of a copper co-catalyst, and the method tolerates synthetically important functional groups. Preliminary mechanistic studies on this Ni-II-catalyzed alkynylation emphasize the homogeneous nature of the catalyst, and rule out a radical manifold for the reaction. The synthetic utility of this Ni-catalyzed method is demonstrated by further functionalizing the alkynylated benzothiazoles to 3-methyl-2-(alkynyl)benzo[d]thiazolium salts that are known DNA cleaving agents.
Keywords: alkynylation; azoles; C-H activation; heterocycles; Nickel

Nickel and cobalt affect galactosylation of recombinant IgG expressed in CHO cells. - Prabhu, A.; Gadgil, M. (BioMetals, 2019)
Glycosylation is an important product quality attribute of antibody biopharmaceuticals. It involves enzymatic addition of oligosaccharides on proteins by sequential action of glycosyltransferases and glycosidases in the endoplasmic reticulum and golgi. Some of these enzymes like galactosyltransferase and N-acetylglucosaminyltransferase-I require trace metal cofactors. Variations in trace metal availability during production can thus affect glycosylation of recombinant glycoproteins such as monoclonal antibodies. Variability in trace metal concentrations can be introduced at multiple stages during production such as due to impurities in raw materials for culture medium and leachables from bioreactors. Knowledge of the effect of various trace metals on glycosylation can help in root-cause analysis of unintended variability in glycosylation. In this study, we investigated the effect of nickel and cobalt on glycosylation of recombinant IgG expressed in Chinese hamster ovary cells. Nickel concentrations below 500 µM did not affect glycosylation, but above 500 µM it significantly decreases galactosylation of IgG. Cobalt at 50 µM concentration causes slight increase in G1F glycans (mono galactosylated) as previously reported. However, higher concentrations result in a small increase in G0F (non galactosylated) glycans. This effect of nickel and cobalt on galactosylation of recombinant IgG can be reversed by supplementation of uridine and galactose which are precursors to UDP-Galactose, a substrate for the enzymatic galactosylation reaction.
Keywords: cobalt; Galactosylation; glycosylation; Nickel; Process variability; Trace metals

Nickel-catalyzed straightforward and regioselective C-H alkenylation of indoles with alkenyl bromides: scope and mechanistic aspect - Jagtap, Rahul A.; Vinod, C. P.; Punji, Benudhar (ACS Catalysis, 2019)
Nickel-catalyzed regioselective C-H bond alkenylation of indoles and related heteroarenes with alkenyl bromides is accomplished under relatively mild conditions. This method allows the straightforward synthesis of C-2 alkenylated indoles employing an air-stable and well-defined nickel catalyst, (bpy)NiBr2, providing a solution to the limitations associated with hydroindolation and oxidative alkenylation. The reaction conceded the coupling of indole derivatives with various alkenyl bromides, such as aromatic and heteroaromatics, alpha- and beta-substituted as well as exo- and endo-cyclic alkenyl compounds. An extensive mechanistic investigation, including controlled study, reactivity experiments, kinetics and labeling studies, and EPR and XPS analyses, highlights that the alkenylation proceeds through a single-electron transfer process comprising an odd-electron oxidative addition of alkenyl bromide. Furthermore, the alkenylation operates via a probable Ni(I)/Ni(III) pathway involving the rate-limiting C-H nickelation of indole.
Keywords: alkenylation; C-H activation; indoles; Mechanism; Nickel; single-electron transfer

Expeditious and solvent-free nickel-catalyzed c-h arylation of arenes and indoles (vol 10, pg 2242, 2017) - Jagtap, Rahul A.; Soni, Vineeta; Punji, Benudhar (ChemSusChem, 2020)
Keywords: Arylation; C-H activation; heterocycles; Homogeneous catalysis; Nickel

Active nickel hollow nanosphere supported over SiO2 catalyst for reduction of nitro compound - Pawar, Priyanka S.; Lokhande, Aboli A.; Nandanwar, Sachin U.; Niphadkar, Prashant S.; Bokade, Vijay V. (Particulate Science and Technology, 2021)
Nickel hollow nanospheres (Ni HNSs) was prepared by solvothermal method using mixture of ethylenediamine (EN) and ethanol (ET), sodium borohydride as reducing agent and nickel chloride hexahydrate as precursor. The particle size of the Ni HNSs were tuned by varying several parameters including precursor concentrations, reaction temperatures (130-190 degrees C), and ET to EN volume ratios. The particle size and morphology of Ni HNSs were confirmed by dynamic light scattering and transmission electron microscope, respectively. Spherical shape of Ni nanoparticles of 300 nm size having similar to 200 nm hollow space and 50 nm thickness was achieved at optimize condition of 4:6 volume ratio of ET/EN, 150 degrees C temperature, 0.1 M NaBH4 concentration, and 7 h. Ni HNSs supported over SiO2 (Ni HNSs/SiO2) with different loading of Ni HNSs (1-10 wt.%) were prepared by impregnation method. The catalyst was characterized by X-ray diffraction, and inductively coupled plasma - optical emission spectroscopy. The catalytic performance of Ni HNSs/SiO2 was carried out in the reduction of 4-Nitrophenol (4-NP) to 4 - Aminophenol (4-AP). 5 wt.% Ni HNSs/SiO2 exhibited 87% reduction of 4-NP in 25 min and stable up to 6 catalyst cycles due to higher surface area of the catalyst.
Keywords: 4-Aminophenol; 4-nitrophenol; Catalyst; hollow nanospheres; Nanoparticles; Nickel

Nickel-catalyzed C-H bond functionalization of azoles and indoles - Jagtap, Rahul A.; Punji, Benudhar (Chemical Record, 2021)
Direct C-H functionalization of privileged and biologically relevant azoles and indoles represents an important chemical transformation in molecular science. Despite significant progress in the palladium-catalyzed regioselective C-H functionalization of azoles and indoles, the use of abundant and less expensive nickel catalyst is underdeveloped. In the recent past, the nickel-catalyzed regioselective C-H alkylation, arylation, alkenylation and alkynylation of azoles and indoles have been substantially explored, which can be applied to the complex organic molecule synthesis. In this Account, we summarize the developments in nickel-catalyzed regioselective functionalization of azoles and indoles with a considerable focus on the reaction mechanism.
Keywords: azoles; C-C Bond formation; C-H functionalization; indoles; Nickel

Ni(II)-catalyzed intramolecular C-H/C-H oxidative coupling: an efficient route to functionalized cycloindolones and indenoindolones - Ankade, Shidheshwar B.; Samal, Pragnya Paramita; Soni, Vineeta; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2021)
Nickel(II)-catalyzed intramolecular C(sp(2))-H/C(sp(3))-H and C(sp(2))-H/C(sp(2))-H oxidative couplings in indoles are achieved via chelation assistance. These reactions provide access to biologically relevant five- and six-membered substituted cyclopentaindolones, carbazolones, and indenoindolones in high yields and good chemoselectivity employing an air-stable and defined nickel catalyst, (bpy)Ni(OAc)(2). The oxidative cyclizations proceeded either through a six-membered or an unconventional seven-membered nickelacycle. An extensive mechanistic investigation by experiments and theoretical calculations revealed a facile indole's C(2)-H nickelation and a rate-limiting reductive elimination process. This intramolecular oxidative cyclization operates via a probable Ni(II)/Ni(III) pathway involving single-electron oxidation of nickel without the participation of a carbon-based radical.
Keywords: C-H activation; cycloindolones; indenoindolones; indoles; Mechanism; Nickel; oxidative coupling

Hydrogenation of levulinic acid to gamma-valerolactone over nickel supported organoclay catalyst - Kamble, Paresh A.; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (Catalysis Today, 2023)
In this work, a series of Ni/Organoclay catalysts with different Nickel loadings were prepared by the wetimpregnation method for the catalytic hydrogenation of levulinic acid (LA) to gamma-valerolactone (GVL). Reaction parameters such as reaction temperature, pressure, solvent effect, and wt% of catalyst were optimized to get excellent conversion of levulinic acid selectively to gamma-valerolactone. Ni/Organoclay with 30% Nickel loading exhibited 100% conversion of LA with 100% selectivity towards GVL at 140 degrees C and 3.0 MPa H2 pressure using 1,4-dioxane as a solvent in 5 h. Different bulk and surface characterization techniques such as XRD, BET, FE-SEM, HR-TEM, XPS, XRF, NH3-TPD, and H2-Chemisorption were used to characterize the Ni/Organoclay catalyst. BET and NH3-TPD analysis showed that the pre-treatment of bentonite with surfactant (CTAB) improved the pore volume, surface area, and acidity of Organoclay which assisted in improving the conversion and selectivity of LA and GVL respectively.
Keywords: ?-Valerolactone (GVL); Bentonite; Hydrogenation; Levulinic acid (LA); Nickel; organoclay

Hydrogenation of furfural to tetrahydrofurfuryl alcohol over nickel-supported on organoclay catalyst - Kamble, Paresh A.; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (Applied Catalysis A-General, 2024)
Nickel supported on organoclay prepared by the impregnation method provides excellent catalytic activity for the hydrogenation of furfural to tetrahydrofurfuryl alcohol. The relative amount of metal and acidic sites influences the hydrogenation reaction. Additionally, by varying the temperature and the H-2 pressure, we can regulate the interaction of furfural with the active sites. And this may decide the fate of the reaction whether it will undergo a two-step hydrogenation to form tetrahydrofurfuryl alcohol or a rearrangement reaction to form cyclopentanone/cyclopentanol. Water was found to be the best solvent for the selective formation of tetrahydrofurfuryl alcohol. Even though alcohols inhibited rearrangement reaction, the hydrogenation of furfural was more selective towards furfuryl alcohol. Ni/O-clay30A under the optimum conditions of 120 degrees C, 4.0 MPa, and in 1 h offered complete conversion of furfural to tetrahydrofurfuryl alcohol.
Keywords: furfural; Hydrogenation; Nickel; organoclay; Tetrahydrofurfuryl alcohol

Hydrogenation of glucose to sorbitol by using nickel hydroxyapatite catalyst - Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra K.; Lakshmi Kantam, Mannepalli (Chemcatchem, 2024)
A series of nickel hydroxyapatite catalysts were synthesized by the co-precipitation method followed by calcination and reduction. These catalysts were employed for the aqueous phase hydrogenation of glucose to sorbitol. The Ni-HAP catalyst with comparatively high surface area and acid-base strength gave high sorbitol selectivity in 1 h. Ni-HAP-4 catalyst with moderate Ni (3.5 wt. %) content having smaller and highly dispersed nickel particles gives an excellent yield of sorbitol, 97 % in 1 h. The Ni-HAP-4 catalyst works well with other polar protic solvents. Different characterization techniques like XRD, TEM, SEM-EDS, BET, NH3-TPD, and CO2-TPD were employed to analyze the Ni-HAP-4 catalyst. A facile hydrogenation of glucose to sorbitol has been reported with Ni-HAP catalyst using water as a solvent. The excellent yield of sorbitol, 97 % in 1 h is possible due to the high surface area and high acid-base strength of the Ni-HAP-4 catalyst. image
Keywords: glucose; Hydrogenation; Hydroxyapatite (HAP); Nickel; Sorbitol

Nickel-catalyzed branch-selective C-H alkylation of indoles and azoles with alkenes: an additive- and solvent-free approach - Ankade, Shidheshwar B.; Banerjee, Shuvajit; Punji, Benudhar (European Journal of Organic Chemistry, 2024)
The development of sustainable protocols for the synthesis of alkylated heteroarenes is crucial owing to their widespread existence in medicinally relevant and bioactive natural products. Herein, we describe an efficient, additive- and solvent-free approach for the regioselective C-H alkylation of indoles and azoles with alkenes using a nickel catalyst, which proceeds through a chelation-assistance strategy. The reaction exclusively provided branched alkylated products with the compatibility of alkyl, alkoxy, fluoro, trifluoromethyl, alkene, cyano, ester, and carbonyl groups. This protocol is applicable to other heteroarenes, such as imidazoles and benzimidazoles, providing the desired alkylated products with exclusive Markovnikov selectivity. The synthetic utility and scale-up of the reaction are demonstrated, and the protocol is in concord with the principles of green chemistry. Alkylation proceeds through facile and reversible C-H nickelation and alkene insertion processes, presumably involving rate-limiting reductive elimination. A straightforward nickel-catalyzed protocol for the C-H alkylation of indoles and azoles is disclosed that proceeds under additive- and solvent-free conditions. The reaction utilizes readily available alkenes as alkylating partners and delivers Markovnikov products with tolerance of sensitive functionalities. image
Keywords: Alkylation; branch selectivity; indoles; Nickel; solvent-free synthesis

Nickel-catalyzed chemodivergent coupling of alcohols: efficient routes to access α,α-disubstituted ketones and α-substituted chalcones - Bansal, Sadhna; Punji, Benudhar (Chemistry- a european journal, 2024)
Chemodivergent (de)hydrogenative coupling of primary and secondary alcohols is achieved utilizing an inexpensive nickel catalyst, (6-OH-bpy)NiCl2. This protocol demonstrates the synthesis of branched carbonyl compounds, alpha,alpha-disubstituted ketones, and alpha-substituted chalcones via borrowing hydrogen strategy and acceptorless dehydrogenative coupling, respectively. A wide range of aryl-based secondary alcohols are coupled with various primary alcohols in this tandem dehydrogenation/hydrogenation reaction. The nickel catalyst, along with KOtBu or K2CO3, governed the selectivity for the formation of branched saturated ketones or chalcones. A preliminary mechanistic investigation confirms the reversible dehydrogenation of alcohols to carbonyls via metal-ligand cooperation (MLC) and the involvement of radical intermediates during the reaction. The chemodivergent nickel-catalyzed approach provides alpha,alpha-disubstituted ketones from aryl-substituted secondary alcohols and benzyl alcohols via the borrowing hydrogen (BH) strategy in the presence of KOtBu, whereas exclusively alpha-substituted chalcones were accomplished in the presence of mild base K2CO3 through an acceptorless dehydrogenative coupling (ADC) strategy. image
Keywords: Alcohols; dehydrogenative coupling; Metal-ligand cooperation; Nickel; substituted carbonyl compounds

Tridentate NacNac tames T-shaped nickel(I) radical - Pahar, Sanjukta; Sharma, Vishal; Raj, K. Vipin; Sangole, Mayur P.; George, Christy P.; Singh, Kirandeep; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry- a european journal, 2024)
The reaction of a nickel(II) chloride complex containing a tridentate beta-diketiminato ligand with a picolyl group [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]Ni(II)Cl (1)] with KSi(SiMe3)3 conveniently afforded a nickel(I) radical with a T-shaped geometry (2). The compound's metalloradical nature was confirmed through electron paramagnetic resonance (EPR) studies and its reaction with TEMPO, resulting in the formation of a highly unusual three-membered nickeloxaziridine complex (3). When reacted with disulfide and diselenide, the S-S and Se-Se bonds were cleaved, and a coupled product was formed through carbon atom of the pyridine-imine group. The nickel(I) radical activates dihydrogen at room temperature and atmospheric pressure to give the monomeric nickel hydride. A thermally stable, T-shaped, nickel(I) radical was straightforward obtained by reduction of a tridentate nacnac nickel(II) chloride with KSi(TMS)3. The metalloradical character of the compound was demonstrated by the formation of a highly unusual nickeloxaziridine complex upon addition of TEMPO. The Ni(I) species displays a rich chemistry towards activation S-S, and Se-Se bond leading to unusual C-C coupled product as well as dihydrogen activation at room temperature and atmospheric pressure to generate monomeric nickel hydride.+image
Keywords: C-C Bond formation; Hydrogen Activation; Metalloradical; Nickel; Tridentate nacnac

Catalytic hydrogenation of cinnamaldehyde over nanocrystalline nickel-doped lanthanum aluminate: synergistic effect of nickel and oxygen vacancies - Bhavisha, Meloth; Balamurugan, Sarkarainadar; Venkatesha, Naragalu J.; Gopinath, Chinnakonda S.; Sakthivel, Ayyamperumal (ChemCatChem, 2025)
Nickel-doped lanthanum aluminium perovskite, LaAl1-xNixO3-delta with x = 0, 0.1, 0.2, 0.3, 0.4,0.5, 0.6, and 0.75 (LANx), were obtained through a combustion method followed by a calcination process. The obtained LANx materials crystallized in the cubic structure by the Pm-3m (221) space group. The nanocrystalline nature of the LANx materials was confirmed by the average crystalline size determined using Debye-Scherrer formula. X-ray photoelectron spectroscopy (XPS) studies showed that nickel was present in the +2 and +3 oxidation states. The introduction of nickel resulted in distinct peaks in TPR in the temperature range of 200-600 degrees C, with an enhanced reducibility of the materials. The LANx materials were thoroughly assessed for their effectiveness in the hydrogenation of cinnamaldehyde. The maximum catalytic activity (cinnamaldehyde conversion of 98% with a hydrocinnamylalcohol selectivity 96.5%) was observed with the presence of the LAN7 catalyst at 150 degrees C for 6 h at a H2 pressure of 10 bar. The catalytic activity is maintained even after four cycles, which broadens the application scope as the material is sustainable, scalable, cost-effective, and a potential alternative to reported noble metal catalysts. The synergistic effect of nickel and oxygen vacancies in the catalyst improves the reducibility and provides a promising catalytic activity in the cinnamaldehyde hydrogenation.
Keywords: Cinnamaldehyde; Hydrocinnamylalcohol; Hydrogenation; Nickel; Perovskite oxide

Hybrid pincer (PNN)Ni(II) complex catalyzed selective C-H alkylation of pyridones using unactivated alkyl chlorides - Verma, Suryadev K.; Samal, Pragnya Paramita; Pradhan, Chandini; Pandey, Dilip K.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2025)
The use of readily accessible unactivated alkyl chlorides in the alkylation reaction to install valuable alkyl and methyl motifs into privileged heterocycles is an underdeveloped area. Herein, we report the regioselective C-H alkylation of diverse pyridones employing challenging unactivated alkyl chlorides as coupling partners, enabled by a strategically developed quinolinyl-based pincer (Ph2PNNQ)Ni(II) complex. The air-stable nickel catalyst is highly effective for the selective alkylation of functionalized 2-pyridones with both primary and secondary alkyl chlorides as well as for the unexpected C6 methylation, furnishing a wide range of 6-alkyl-2-pyridone scaffolds (78 examples). Remarkably, the alkyls bearing biologically and pharmacologically significant motifs, such as pterostilbene, nonyl phenol, sesamol, estrone, vitamin E, stigmasterol, cholesterol, and diosgenin, were compatible under this catalytic approach. The insights into the mechanism suggest that the alkylation reaction follows a Ni(II)/Ni(III)/Ni(IV) pathway involving the crucial two-step, one-electron oxidative addition of alkyl chloride. Several control studies, kinetics, and EPR analyses were performed to understand the detailed reaction pathway, further supported by density functional theory calculations.
Keywords: alkyl chlorides; C-H/C-Cl activation; hybrid pincer ligand; Mechanism; Nickel; pyridones

Nickel-catalyzed regioselective C―H alkynylation of pyridones and isoquinolinones using alkynyl bromides - Verma, Suryadev K.; Patil, Harshal R.; Punji, Benudhar (ChemCatChem, 2025)
A straightforward and efficient protocol for the regioselective C & horbar;H alkynylation of 2-pyridones and isoquinolinones with bromoalkynes under nickel catalysis is described. The alkynylation reaction is enabled by a simple and inexpensive Ni(OTf)2/tBubpy catalyst system and uses easily accessible bromoalkynes. The protocol demonstrates a broad substrate scope with up to 95% yield (42 examples) and accommodates synthetically valuable functionalities, such as halides, trifluoromethyl, nitrile, ether, thioether, alkyl silanes, and alkene, as well as heteroarene moieties like pyridinyl, furanyl, and thiophenyl. The pyridinyl directing group on alkynylated 2-pyridones can be smoothly removed to give C6-alkynylated free NH-pyridone. Preliminary mechanistic studies suggest that the alkynylation proceeds via a 2e- oxidative addition pathway involving crucial C & horbar;H activation.
Keywords: alkynylation; C & horbar; H Activation; Mechanism; Nickel; pyridones

Regioselective difluoroalkylation of 2-pyridones with fluoroalkyl bromides enabled by a nickel(II) catalyst - Pradhan, Chandini; Khandelwal, Disha; Punji, Benudhar (Chemistry-An Asian Journal, 2025)
Regioselective C-H difluoroalkylation of diverse 2-pyridones with ethyl bromodifluoroacetates and bromodifluoroacetamides is accomplished by using a (dppf)NiCl2 catalyst under mild conditions. This efficient protocol could deliver a variety of C-3 difluoroalkylated pyridones with the tolerance of a range of highly susceptible functionalities, such as -Cl, -Br, -I, -COMe, -CN, -NMe2 and -NO2, including heteroarenes like pyridinyl, furanyl, thiophenyl and carbazolyl moieties. A preliminary mechanistic study suggests the radical pathway for the reaction involving fluoroalkyl radical intermediate.
Keywords: 2-pyridones; Difluoroalkylation; Nickel; radical intermediate; Regioselectivity

(NHC-olefin)-nickel(0) nanoparticles: an efficient and selective catalyst for hydrogenation reactions at low temperature and pressure - Avello, Marta G.; Singh, Geetika; Truong-Phuoc, Lai; Vidal, Loic; Papaefthimiou, Vasiliki; Chesse, Matthieu; Gruber, Nathalie; Chetcuti, Michael J.; Vanka, Kumar; Ritleng, Vincent; Pham-Huu, Cuong; Michon, Christophe (Journal of Catalysis, 2026)
The reduction of a NHC-cinnamyl nickel(II) organometallic complex through the use of different MeMgBr or MeMgCl reagents led to two types of NHC-olefin-coordinated nickel nanoparticles. Both of these unsupported nickel-NHC based nanomaterials behaved under hydrogen pressure as effective and selective catalysts operating at low temperature (<= 80 degrees C), pressure (<= 20 bar) and loading (<= 6 mol%) for the reductions of broad scopes of alkenes, alkynes, imines and heterocycles, including a challenging tetra-substituted alkene. Among these two nickel-NHC nanocatalysts, the one generated with MeMgCl showed a significant high catalytic activity with high yields and could stand the comparison with Raney nickel and state-of-the-art nickel nanocatalysts. For example, by studying the hydrogenation of 1-phenylcyclohexene in ethanol at 60 degrees C under 10 bar of H2, 3 mol% of this catalyst achieved the reaction within a single hour on a 5 mmol/0.8 g substrate scale with a yield of 96 %, a turnover number (TON) of 32 and a turnover frequency (TOF) of 32. Characterizations confirmed the coordination of the NHC-olefin ligands to the nickel nanoparticles, the reduced state of the nickel and the (poly-) crystallinity of the nanoparticles.
Keywords: alkenes; Alkynes; heterocycles; Hydrogenation; imines; N -heterocyclic carbene ligand; nanocatalysis; Nickel